Relationship between Plasma Fibronectin Levels and Stretch Marks - Syahputri, Fitriend; Imam Budi Putra; Nelva K. Jusuf (CoinReads Media Prima, 2024)
Introduction: Stretch marks or striae distensae are linear atrophic scars that form in areas of skin damage as a result of skin stretching. Mast cell degranulation and activation of macrophages occur as well as changes in the components of the extracellular matrix, including fibronectin. Fibronectin as a dimeric glycoprotein and components contained in the extracellular matrix, functions as a regulator of cellular processes, to maintain tissue and functions in the process of wound healing in tissues. The aim of this study was to determine the relationship between plasma fibronectin levels and stretch marks Methods: This study was an observational study with a cross-sectional design of 40 females with stretch marks and 40 controls. Each patient underwent history, dermatological examination, and blood sampling to assess plasma fibronectin levels by ELISA test. These data were analyzed statistically using the Chi square test. Results: The mean plasma fibronectin level in stretch marks was 259.541±165.937 ng/ml. The highest age with stretch marks was 18–25 years 33 (82.5%) people. Most of them had a family history of stretch marks from their mother 20 (50%) people. The majority of stretch marks are located on gluteus regions by 10 people (25%). The result of this study showed that there was a relationship between plasma fibronectin levels causing a risk of 2.85 times for stretch marks (p = 0.041). Conclusion: There is a relationship between plasma fibronectin levels and stretch marks.